The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5005/jp-journals-10071-23719
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Arterial Blood Gas Test in an Intensive Care Unit: An Observational Study

Abstract: A bstract Background Arterial blood gas (ABG) analysis is a common test ordered in critically ill patients. Often, it is performed very frequently without influencing patient care. Hence, we decided to check the utility of the ABG test in our intensive care unit (ICU). Materials and methods The data of the previous day ABGs were captured by reviewing the chart in an online pro forma which was filled by the authors. Data relating to patient's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In one study, up to 80% of ABGs were sent based on "routine" practice with no clinical treatment performed based on test results. 20 In a level one trauma center that performed targeted education, the number of ABGs sent was reduced by 33%, representing an annual cost savings of $700,000 and reduction in phlebotomy volume of 100 liters of blood. 21 Blood draws are frequently performed to assess anticoagulation status during ECMO and over-anticoagulation can contribute to bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, up to 80% of ABGs were sent based on "routine" practice with no clinical treatment performed based on test results. 20 In a level one trauma center that performed targeted education, the number of ABGs sent was reduced by 33%, representing an annual cost savings of $700,000 and reduction in phlebotomy volume of 100 liters of blood. 21 Blood draws are frequently performed to assess anticoagulation status during ECMO and over-anticoagulation can contribute to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Many ABGs are sent without actionable consequence in critically ill patients. In one study, up to 80% of ABGs were sent based on “routine” practice with no clinical treatment performed based on test results 20 . In a level one trauma center that performed targeted education, the number of ABGs sent was reduced by 33%, representing an annual cost savings of $700,000 and reduction in phlebotomy volume of 100 liters of blood 21 …”
Section: Discussionmentioning
confidence: 99%
“…An arterial blood gas (ABG) test is one of the most frequently performed tests in intensive care units (ICU). It is the most accurate method of assessing the oxygenation level by determining the level of oxygen pressure in arterial blood (PaO 2 ) [6,7]. The ABG test is used to detect hypoxia (0-80 mm Hg), normoxia (80-100 mm Hg), and hyperoxia (> 100 mm Hg), but it can also be used to measure parameters such as the level of carbon dioxide pressure in arterial blood (PaCO 2 ), pH, concentration of bicarbonate in arterial blood (HCO 3 -), and excess or deficit of base in arterial blood (BE), thus allowing the assessment of ventilation and the body's acid-base balance [8].…”
Section: Arterial Blood Gas Testmentioning
confidence: 99%
“…A recent study has shown that PaO 2 ∗ 10/FiO 2 ∗ PEEP (P/FP ∗ 10 ratio) has a significantly better predictive ability for mortality in ARDS patients when compared to P/F ratio alone [ 2 ]. However, as these values change dynamically during the course of mechanical ventilation (MV) in a patient, repeated arterial sampling is required which is associated with increased chances of infection, blood loss, patient discomfort, and costs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%